PENGARUH STRUKTUR MODAL, LIKUIDITAS, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2022-2024 - Rolasni Roha Purba; Mahmuddin Syah Lubis; Yusneni Afrita Nasution (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This research aims to analyze the impact of financial variables on food and beverage issuers on the Indonesia Stock Exchange (IDX) for the 2022-2024 period, both individually and collectively. The research is based on the crucial importance of corporate performance as a parameter of business success and investor interest, coupled with the existence of discrepancies in previous research findings regarding the elements influencing such performance. This study employs quantitative methods, employing description and verification. Subjects were selected based on specific criteria from the list of manufacturing companies on the stock exchange. The information analyzed includes capital ratios, liquidity, and company scale and age profiles. The research results are projected to reveal whether these variables have a significant impact, either independently or simultaneously, on company performance. Thirty-six food manufacturing issuers on the IDX were sampled from 2022 to 2024, utilizing SPSS statistical software. The final findings indicate that capital ratios have no significant impact on the performance of manufacturing issuers on the stock exchange. Conversely, liquidity significantly contributes to the business results of manufacturing companies on the stock exchange. Corporate scale also significantly influences the performance of publicly traded manufacturing companies. Finally, company age has been shown to have a crucial impact on the business performance of manufacturing companies listed on the IDX.